2020
DOI: 10.7717/peerj.10196
|View full text |Cite
|
Sign up to set email alerts
|

Upper-room ultraviolet air disinfection might help to reduce COVID-19 transmission in buildings: a feasibility study

Abstract: As the world’s economies come out of the lockdown imposed by the COVID-19 pandemic, there is an urgent need for technologies to mitigate COVID-19 transmission in confined spaces such as buildings. This feasibility study looks at one such technology, upper-room ultraviolet (UV) air disinfection, that can be safely used while humans are present in the room space, and which has already proven its efficacy as an intervention to inhibit the transmission of airborne diseases such as measles and tuberculosis. Using p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 56 publications
(96 reference statements)
1
52
1
Order By: Relevance
“…The attention paid to hygiene practices towards the body and the surfaces has led to several modifications in human habits and to the development of innovative and efficient cleaning procedures. As well as the chemical ones, physical disinfection methods may be rapid and less time-consuming thanks to the possibility for them to be exerted by automated instruments and to the possibility of being carried out on solid surfaces and aerosols [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attention paid to hygiene practices towards the body and the surfaces has led to several modifications in human habits and to the development of innovative and efficient cleaning procedures. As well as the chemical ones, physical disinfection methods may be rapid and less time-consuming thanks to the possibility for them to be exerted by automated instruments and to the possibility of being carried out on solid surfaces and aerosols [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, beyond the standard disinfection methods such as chemical ones, ultraviolet germicidal irradiation (UVGI) has a potential role. In particular, UV-C light at wavelengths of about 254 nm exerts bactericidal and virucidal effects, and it is widely used in the environmental disinfection of enclosed spaces [ 14 ]. UV-C light induces chemical modifications of nucleic acids, leading to the blocking of replication mechanisms [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, directly applying the UV rate constant extracted from Table 1 will underestimate the UVGI performance (lower UV rate constant of microbes in water than in aerosols). To convert available laboratory data from the liquid phase to the aerosol phase, some studies introduced a species-dependent concept of “UV rate constant ratio of aerosol and liquid” to correlate the UV rate constant of a group of the same types of viruses in different phases [ 57 , 63 ]. Using this methodology, researchers estimated that the UV rate constant of the coronavirus in air is 1.8–6.0 times higher than that in liquid [ 63 ].…”
Section: Uvgi Fundamentalsmentioning
confidence: 99%
“…Using published data from various sources, it is shown that the SARS coronavirus-2, the causative agent of COVID-19, is highly likely to be susceptible to UI-C damage when suspended in air, with a UI susceptibility constant likely to be in the region 0.377–0.590 m 2 J −1 , similar to that for other aerosolized coronaviruses ( Beggs et al, 2020 ).…”
Section: Uimentioning
confidence: 93%